Electroanalytical determination of two ACCase-inhibing herbicides in soybean products. A theoretical insight - Volodymyr Tkach,; Morozova, Tetiana; Ferrão da Paiva Martins, José Inácio; O´Neill de Mascarenhas Gaivão, Isabel; Ivanushko, Yana; Turkmenoglu, Mehmet; Yagodynets, Petro (Orbital: The Electronic Journal of Chemistry, 2025)
This study evaluates the possibility of electroanalytical detection of clethodim and fenoxaprop-p-ethyl in soybean crops and products. The electrochemical analysis may be performed at both the cathode and the anode, given the presence of donor and acceptor functional groups. Two mathematical models, each for the positive or negative polarity of the working electrode, were developed and analyzed using linear stability theory and bifurcation analysis. Either way, the electroanalytical behavior is effective and sufficient to quantify the nanomolar concentrations of both pesticides. However, considering the moderately acidic environment of the soybean plant and its products, the cathodic process is preferable.